2017
DOI: 10.2334/josnusd.16-0372
|View full text |Cite
|
Sign up to set email alerts
|

Stimulated salivary flow rate and oral health status

Abstract: This study examined the relationship between stimulated salivary flow rate and oral health status in an adult population. Multinomial multivariate logistic regression analysis was used to examine the associations of salivary flow rate with dental caries status and periodontal status at the individual level among 2,110 Japanese adults with ≥10 teeth. Then, a spline model was used to examine the nonlinear relationship between salivary flow rate and teeth with dental caries or periodontal disease in multilevel an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
28
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 27 publications
5
28
0
5
Order By: Relevance
“…There is great variability in the interindividual salivary VFR; the accepted range of a normal VFR for stimulated saliva production ranges from 2000 to 70,000 mm 3 /10 min. 2,28,29 The mean VFR in our human study was 8760 mm 3 /10 min and therefore within the reported range. Moreover, the VFR (minimum VFRmax: 2850 mm 3 /10 min) in all volunteers was higher than the minimum accepted VFR.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…There is great variability in the interindividual salivary VFR; the accepted range of a normal VFR for stimulated saliva production ranges from 2000 to 70,000 mm 3 /10 min. 2,28,29 The mean VFR in our human study was 8760 mm 3 /10 min and therefore within the reported range. Moreover, the VFR (minimum VFRmax: 2850 mm 3 /10 min) in all volunteers was higher than the minimum accepted VFR.…”
Section: Discussionsupporting
confidence: 86%
“…The mean VFR over 10 minutes, calculated from mean VFRmax, was 8760 mm 3 . There is great variability in the interindividual salivary VFR; the accepted range of a normal VFR for stimulated saliva production ranges from 2000 to 70,000 mm 3 /10 min . The mean VFR in our human study was 8760 mm 3 /10 min and therefore within the reported range.…”
Section: Discussionsupporting
confidence: 72%
“…The increase of salivary flow is much more effective in neutralizing and buffering food acids. The study by Shimazaki et al reveals that decreased saliva secretion affects both dental caries and general periodontal health status 21 . Ahmad et al also reported that hyposalivation due to the low saliva flow rate related to more caries in the aging population and significantly poor of the quality of life 22 .…”
Section: Amendments From Versionmentioning
confidence: 99%
“…Though, the actual information regarding the conditions associated with the production of the saliva is limited. 5 Using the salivary flow rate, saliva's quantitative state is determined. The salivary flow rate is the measurement of production of the saliva in a given period of time by the salivary gland which is expressed usually in grams per minute or milliliters per minute (g/min or mL/min).…”
mentioning
confidence: 99%